2022
DOI: 10.1038/s42003-021-02958-6
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1 expression is associated with high-risk neuroblastoma and promotes primary and metastatic tumor growth

Abstract: The embryonic transcription factors TWIST1/2 are frequently overexpressed in cancer, acting as multifunctional oncogenes. Here we investigate their role in neuroblastoma (NB), a heterogeneous childhood malignancy ranging from spontaneous regression to dismal outcomes despite multimodal therapy. We first reveal the association of TWIST1 expression with poor survival and metastasis in primary NB, while TWIST2 correlates with good prognosis. Secondly, suppression of TWIST1 by CRISPR/Cas9 results in a reduction of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“… 648 Twist is expressed in mesodermal and ectodermal-derived tissues, and it has been found that Twsit1 and Twsit2 which are structurally homologous are overexpressed in multiple human cancers. 647 , 648 Twsit1 overexpression has been confirmed to be strongly associated with aggressiveness and metastasis in cancer patients, including sarcoma, glioma, melanoma, ESCC, 649 neuroblastoma, 650 cervical cancer, 651 RCC, 652 and hematological malignancies including AML, chronic myeloid leukemia (CML), ALL, CLL, lymphomas. 653 In CML patients, the increased expression of Twist is related to tumor progression, tumor staging, and drug resistance, and Twist can be applied as a biomarker to assess MRD.…”
Section: Classification Of Tumor Biomarkersmentioning
confidence: 99%
“… 648 Twist is expressed in mesodermal and ectodermal-derived tissues, and it has been found that Twsit1 and Twsit2 which are structurally homologous are overexpressed in multiple human cancers. 647 , 648 Twsit1 overexpression has been confirmed to be strongly associated with aggressiveness and metastasis in cancer patients, including sarcoma, glioma, melanoma, ESCC, 649 neuroblastoma, 650 cervical cancer, 651 RCC, 652 and hematological malignancies including AML, chronic myeloid leukemia (CML), ALL, CLL, lymphomas. 653 In CML patients, the increased expression of Twist is related to tumor progression, tumor staging, and drug resistance, and Twist can be applied as a biomarker to assess MRD.…”
Section: Classification Of Tumor Biomarkersmentioning
confidence: 99%
“…Twist1 is a highly conserved member of the basic helix-loop-helix proteins and is responsible for the transcriptional regulation of mesenchymal cell lineages [ 21 ]. Several studies have demonstrated that the overexpression of Twist1 is upregulated in several cancer types including breast, liver, prostate, melanomas, and endometrial cancer [ 28 31 ]. A study by Sun et al has shown that Twist1 expression is correlated with vascular formation in HCC [ 32 ].…”
Section: Introductionmentioning
confidence: 99%